A Maturity Model for the Accredited Food Laboratory in Malaysia: A Case Study - Li Hui Ling; Mohd Sukri Hassan; Che Wan Zanariah Che Wan Ngah; Mehmet Ozturk (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Science Health & Technology, Volume 11 Issue 1 Page (109–121)